Suppose the mass of the moon is Mm and its radius is Rm. If a body of mass m is placed on the surface of moon, then weight of the body on the moon is
Wm = {๐บ๐_๐๐ \over ๐ _๐^{2}}ย โฆ (1)
Weight of the same body on the earth’s surface will be
We = {๐บ๐_๐๐ \over ๐ _๐^2} ย โฆ (2)
where M, = mass of earth and Re radius of earth.
Dividing equation (1) by (2), we get
{๐_๐ \over ๐_๐} = {๐_๐ \over ๐_๐} ร {๐ _๐^2 \over ๐ _๐^2}ย โฆ (3)
Now, mass of the earth, Me = 6 x 1024 kg
mass of the moon, Mm = 7.4 x 1022 kg
radius of the earth, R e = 6400 km
and radius of the moon, Rm = 1740 km
Thus, equation (3) becomes,
= {๐_๐ \over ๐_๐} = {7.4 ร10^{22}kg \over 6ร10^{24}kg} ร ({ 6400 km \over 1740 km}) 2
Or,ย {๐_๐ \over W_ ๐}ย โย {1\over6}
Or, Wm โ {๐_๐ \over 6}
The weight of the body on the moon is about one-sixth of its weight on the earth.